Dari Pembinaan Menuju Kemandirian: Pelatihan Barista untuk Klien Pemasyarakatan - Nurfitriany Fakhri; Abdul Rahmat; Salsa Sani Putri; Andi Nurfadhilah Roskar; Davina Aulia Darsan (Universitas Negeri Makassar, 2026)
This community service activity aimed to improve the knowledge and work skills of correctional clients through barista training at Balai Pemasyarakatan Kelas I Makassar. The activity was carried out using training methods through material presentation, demonstrations, and direct practice in making coffee beverages. Participants consisted of correctional clients who attended the training program. Data collection was conducted using pre-test, post-test, observation, and participant satisfaction evaluation through online forms. Data were analyzed descriptively by comparing the average scores of participants before and after the training. The results showed an increase in participants’ knowledge after attending the training, indicated by the increase in average pre-test and post-test scores and the rise in the number of participants in the high knowledge category. Participant satisfaction evaluation also showed that most participants were satisfied with the implementation of the training activities. The barista training activity was able to improve participants’ understanding, practical skills, self-confidence, and work readiness as preparation for social reintegration and independent economic opportunities after returning to society.